Advances in broadband communication and networks - Agbinya, J. I. (River Publishers Series in Communications, 2008)
Broadband communication has become the major focus for industry for offering rich multimedia IP services in next generation networks. This book deals with the state-of-the-art and the underlying principles of key technologies which facilitate broadband telecommunications, illustrating the use of these technologies.